COURSE PLAN IN ACADEMIC WRITING: ENHANCING GRADE 11 STUDENTS’ WRITTEN DISCOURSE COMPETENCE - Raynand D. Dizon (Galaxy International Interdisciplinary Research Journal, 2021)
The main objective of this study was to design an academic course plan for senior high school, anchored on Jim Cummins’ Common Underlying Proficiency (CUP) and Cognitive Academic Language Proficiency (CALP) concerning the level of respondents’ academic writing performance in English and Filipino in writing argumentative essays. Multistage sampling technique was used to obtain the thirty sampled Grade 11 student respondents from six public secondary schools. A standardized rubric was adopted from The Common Core State Standards Writing Rubrics in 2012 whose components include claim, cohesion, development of ideas (coherence), and style and conventions excluding audience criterion. Correspondingly, quantitative approach using descriptive-correlational design was employed to determine the level of the respondents’ written discourse in composing argumentative essays in Filipino and English. Descriptive design was used to describe the respondents’ ability to write argumentative essays in Filipino and English, while correlational design was utilized as the researcher assessed the relationship of the respondents’ first and second language in terms of writing argumentative essays in Filipino and English. The results revealed that the respondents’ first language (Filipino) written discourse competence did not have significant relationship to their second language (English) written discourse competence in support of Separate Underlying Proficiency (SUP), except for development of ideas in English and claim in Filipino. Likewise, the respondents’ written discourse competence in Filipino (L1) did not predict their written discourse competence in English (L2).